2022
DOI: 10.1021/acs.analchem.2c01627
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative Screening of THC Analogues by Silica Gel TLC with an Ag(I) Retention Zone and Chromogenic Smartphone Detection

Abstract: With the ever-evolving cannabis industry, low-cost and high-throughput analytical methods for cannabinoids are urgently needed. Normally, (potentially) psychoactive cannabinoids, typically represented by Δ9-tetrahydrocannabinol (Δ9-THC), and nonpsychoactive cannabinoids with therapeutic benefits, typically represented by cannabidiol (CBD), are the target analytes. Structurally, the former (tetrahydrocannabinolic acid (THCA), cannabinol (CBN), and THC) have one olefinic double bond and the latter (cannabidiolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…45 However, our attempts to add Δ 8 -THC to this workflow resulted in its coelution with CBD using various chemical modifiers (Figures S2 and S3), indicating that an alternative separation strategy will be required. The successful separation of cannabinoids by flash chromatography employing Ag +impregnated silica implies that argentination could be a viable approach, 57 prompting us to investigate the potential of DMS to separate cannabinoids as [M + Ag] + adducts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…45 However, our attempts to add Δ 8 -THC to this workflow resulted in its coelution with CBD using various chemical modifiers (Figures S2 and S3), indicating that an alternative separation strategy will be required. The successful separation of cannabinoids by flash chromatography employing Ag +impregnated silica implies that argentination could be a viable approach, 57 prompting us to investigate the potential of DMS to separate cannabinoids as [M + Ag] + adducts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…During method development, it was observed that when neat FBBBS solution was used, the spots for particular cannabinoids were very faint, notably for THCA and CBE. Better colour development was then achieved when the plate was made alkaline after FBBBS derivatisation, as has been pointed out elsewhere 26,52 . The best results were obtained when a NaOH 0.1 M solution in MeOH/water 90:10 (v/v) was sprayed after FBBBS.…”
Section: Resultsmentioning
confidence: 59%
“…However, among the few other reported HPTLC methods for C. sativa inflorescences, 30 most are targeting cannabinoid quantitation, such as the reports by Fischedick et al, 36 Duffau et al, 39 Liu et al, 50 and application notes by CAMAG 38,40 . Some recent studies employing the classical TLC format have also been published for cannabis, aiming to improve resolution or selectivity for cannabinoids 51,52 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations